Theileria parva in Zambia: A scoping review protocol - Chishimba M. Mubanga; Choolwe Malabwa; Noreen Machila; Martin C. Simuunza (PLoS ONE, 2026)
Objective The objective of this scoping review is to examine published and unpublished literature on Theileria parva in Zambia. It will identify the scope of available literature for research prioritization. Introduction Theileria parva is the most lethal tick borne disease in Zambia due to its reportedly high morbidity and mortality in cattle. It is a focus of government interventions. It is important to understand the research that has been conducted on this parasite over the years. Inclusion criteria The review will include all studies conducted on Theileria parva in Zambia. Government and research institute reports based on recognized laboratory diagnosis will also be included. Methods Literature search will be conducted in Pubmed, Scopus, Web of knowledge and Embase. Primary studies from 1920 to date will be included. Titles, abstracts and full text will be examined to determine eligibility for inclusion. Extracted data will be charted into a data extraction excel file by two independent reviewers. The results will be summarised and presented as a narrative summary, tables and charts.